Association between genetic evaluation and show-ring judging for dairy and beef cattle - Ramírez Valverde, Rodolfo; Ramírez Valverde, Gustavo; Núñez Domínguez, Rafael; Delgadillo Zapata, Rafael A; Hernández León, Miguel (Revista Colombiana de Ciencias Pecuarias, 2016)
a concern for breeders is whether an animal ranking based on genetic evaluations is similar to that obtained from show-ring judging. Objective: to determine the association between rankings for Braunvieh (BR) and Brown Swiss (BS) cattle of Mexico based on show-ring judging and their respective expected progeny differences (EPDs) or predicted transmitted abilities (PTAs). Methods: ranking values from judging were transformed using the rankit transformation. For each breed, Pearson correlation analyses were performed between the transformed rank values of the animals obtained from judging at the show-ring and their EPD or PTA values. Results: using the complete databases, in both breeds the correlation coefficient estimates were low (< 0.18) but different from zero (p < 0.05). The correlation coefficient considering PTAs for milk yield in BS was slightly higher than those obtained for any EPD for growth traits in BR. Correlations in adult animals (0.18 to 0.23) were different from zero (p < 0.05) and higher than those of young animals or calves, while those within males or females were similar. Correlations within years of judging in the show-ring were variable and did not indicate any specific trend. Conclusions: show-ring rank results are associated with genetic evaluation of animals, although the magnitude is low. Selection of breeding animals based on show-ring judgment could be used as a complementary tool to genetic evaluation.